Pengaruh Iklim Organisasi Dan Disiplin Kerja Terhadap Produktivitas Kerja Guru - Idham Idham; Sofwan Manaf; Muhammad Alfianur; Fuad Ahmad Riva'i; Mastur Mastur (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to determine the influence of organizational climate and work discipline on the work productivity of teachers at SMAN 111 Jakarta. The method used in this study is a quantitative approach with data collection techniques using questionnaires. The results showed that: 1) Organizational climate had a positive and significant effect of 38.8% on teacher work productivity, 2) Work discipline also had a positive and significant effect of 36.2% on teacher work productivity, 3) Simultaneously, organizational climate and work discipline had a positive and significant effect on teacher work productivity by 51.1%.